2021
DOI: 10.1177/21582440211058188
|View full text |Cite
|
Sign up to set email alerts
|

Project Managers’ Competencies in International Development Projects: A Delphi Study

Abstract: Project Managers’ (PMs) competencies are critical issues for international development projects (IDPs), and the success of IDPs is largely dependent on how prudently and effectively a PM manages the IDPs operations. So far, the topic of PMs Competencies is mainly explored in the private sector context using a survey-based research approach, and very few attempts have been made to examine the competencies of PMs in the IDPs sector. Accordingly, this study examines the PMs’ competencies at each phase of the proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…This is consistent with previous works (e.g. Sang et al, 2018;Alvarenga et al, 2019;Bashir et al, 2021;Sampaio et al, 2021) which found the importance of behavioral competencies to project success. However, few studies verified it using empirical quantitative analysis (Gruden and Stare, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous works (e.g. Sang et al, 2018;Alvarenga et al, 2019;Bashir et al, 2021;Sampaio et al, 2021) which found the importance of behavioral competencies to project success. However, few studies verified it using empirical quantitative analysis (Gruden and Stare, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Table 8 presents the list of the competences found. Two competences were identified as unique to this type of project in this study, which are Loyalty [69] and Acceptance [70]. For Gomes et al [69], the competence of Loyalty refers to the ability of the project professional to honor their commitments to subordinates and the organization, and thus be an effective politician.…”
Section: Project Type -Public Governmentmentioning
confidence: 94%
“…For Gomes et al [69], the competence of Loyalty refers to the ability of the project professional to honor their commitments to subordinates and the organization, and thus be an effective politician. According to Bashir et al [70], Acceptance competence refers to the competence of the project professional applied during the project closing phase. Thus, the project professional must be able to manage the acceptance of all documentation and reports delivered by stakeholders.…”
Section: Project Type -Public Governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though literature reviews to determine important competencies (Jokinen, 2005), surveys about perceived development needs (Viitala, 2005) and meta-analyses with implications for developments (Gaddis & Foster, 2015) have been conducted, just what exactly the “right competencies” are remains unclear. According to the literature, competency models can be found for industries (Prifti et al, 2017), specific sectors (Bashir et al, 2021; Ranjbar et al, 2014), hierarchical levels (Kan et al, 2002), positions in the company (Kaur & Bains, 2013), centuries (Rahman, 2012), generations (Harrison, 2015), subgroups such as females (Jaafar et al, 2016), core competencies (Edgar & Lockwood, 2021), as well as general competency frameworks that can be individualized (Midhat Ali et al, 2021). Yet from the abundance of models, it is difficult to determine exactly which competencies are important for specific jobs.…”
Section: Research Gap and Conceptual Developmentmentioning
confidence: 99%